2011
DOI: 10.1590/s1679-45082011rc1676
|View full text |Cite
|
Sign up to set email alerts
|

Livedoid vasculopathy: fast involution after anticoagulant and hyperbaric oxygen therapy

Abstract: The livedoid vasculopathy is a rare condition characterized by the presence of recurrent painful ulcers in distal extremities of lower limbs. Histologically there is thickness of dermal vessels, occlusion of its light by fibrin thrombi associated with minimal inflammatory infiltrate. It might occur as an isolated condition or be associated with an underlying systemic disease, including coagulation and collagen disorders, or neoplasms. Because it is a rare disease there is no consensus for its treatment. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…Table 3 shows the articles from our review of the literature for studies that reported on anticoagulant treatment in LV patients (4 prospective studies, 2 retrospective studies, and 33 case reports) 2,5‐42 . From 39 studies, 219 patients with 139 (63.5%) females and 80 (36.5%) males were included.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the articles from our review of the literature for studies that reported on anticoagulant treatment in LV patients (4 prospective studies, 2 retrospective studies, and 33 case reports) 2,5‐42 . From 39 studies, 219 patients with 139 (63.5%) females and 80 (36.5%) males were included.…”
Section: Resultsmentioning
confidence: 99%
“…In 2003, Yang et al 4 described two patients with an intractable LV whose ulcers were successfully treated with HBOT. After this, other authors published case reports with similarly satisfactory results in LV patients 5‐11 …”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 88%
“…Beberapa kondisi yang berhubungan dengan VL adalah seperti insufisiensi kronik vena, penyakit autoimun jaringan ikat, trombofilia turunan maupun didapat, neoplasma, dan idiopatik. 4,5 Penyakit VL merupakan penyakit yang jarang terjadi, sehingga konsensus terapi yang terbaik pada penyakit ini masih belum ada. Pendekatan terapi pada VL bervariasi dengan respons yang juga bervariasi.…”
Section: Pendahuluanunclassified
“…Penting sekali menginvestigasi kemungkinan beberapa penyebab yang berhubungan dengan VL untuk menentukan terapi. 4,6,7 Methotrexate merupakan salah satu modalitas terapi berupa imunosupresan pada kasus vaskulitis. Investigasi awal bahwa methotrexate digunakan sebagai terapi vaskulitis adalah berdasarkan mekanisme aksinya dan hasil dari beberapa laporan kasus.…”
Section: Pendahuluanunclassified